Menstrual Abnormalities and Associated Hormone Profile In Chronic Kidney Disease Stage 5 Patients (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Although menstrual abnormalities and associated hormonal dysregulations are very common in the reproductive age group of Chronic Kidney Disease (CKD) patients, this remains a neglected area. This field had been poorly explored in last ten years worldwide and a few research regarding this area in Bangladesh as well. Aim: To evaluate menstrual abnormalities occurring in CKD stage 5 (CKD5)patients undergoing twice-weekly and thriceweekly maintenance hemodialysis (HD) also in non-dialytic CKD5 patients and to provide more detail information on hormone profile (FSH, LH, Prolactin, Estradiol) of these patients.Materials and method: This obsevational study was conducted in the Department of Nephrology, DMCH, the sample population was also collected from BSMMU and NIKDU from April 2017 to March 2018. A total of 51 CKD stage 5 patients were enrolled in this study. Among them, 34 patients were dialytic (17 of them were taking twice weekly HD and 17 of them were taking thrice weekly HD) and 17 non-dialytic patients at reproductive age were evaluated. Detailed menstrual histories, thorough clinical examinations as well as investigations were done in all the patients. Serum FSH, LH, Estradiol, and Prolactin were evaluated using chemiluminescence immunoassay in the Department of Microbiology of BSMMU. Statistical analysis of the study was done by SPSS-24. The confidence interval was considered at 95% level. P-value